Fishpathogens.eu/noda: a free and handy online platform for Betanodavirus targeted research and data sharing. Issue 8 (11th April 2015) - Mikkelsen, S S; Panzarin, V; Jonstrup, S P; Bigarré, L; Baud, M; Gray, T; Agapow, P‐M; Olesen, N J
Abstract Viral nervous necrosis (VNN) is a severe neuropathological disease affecting a broad variety of finfish species worldwide. The causative agents of VNN are small viruses with a bi‐segmented RNA genome known as betanodaviruses. At least four species with distinct but yet insufficiently characterized epidemiological features are recognized. The spread of VNN to an increasing number of host species, its wide geographic extent and its economical and ecological impacts justify the importance of collating as much molecular data as possible for tracing the origin of viral isolates and highlight the need for a freely accessible tool for epidemiological and molecular data sharing and consultation. For this purpose, we established a web‐based specific database using the www.fishpathogens.eu platform, with the aim of collecting molecular and epidemiological information on VNN viruses, with relevance to their control, management and research studies.